CAR T-cells meet autoimmune neurological diseases: a new dawn for therapy - Chinas, Nikolaos A.; Alexopoulos, Harry (Frontiers in Immunology, 2025)
Autoimmunity and autoimmune diseases arise when the immune system erroneously targets self-antigens leading to tissue damage. Consequently, immunomodulatory and mainly immunosuppressive drugs comprise the conventional treatment in conditions such as systemic lupus erythematosus, rheumatoid arthritis and multiple sclerosis. However, many of these agents often fall short of providing a cure and have a limit on symptom management. This underscores the urgent need for even more advanced therapies for patients to constrain progressive disability. Therefore, currently, researchers explore the potential of chimeric antigen receptor (CAR) T-cell therapy for autoimmune diseases considering its success in cancer treatment and specifically in hematological malignancies. This review will examine recent advancements in CAR T-cell therapy for autoimmune disorders, highlighting how CAR T cells can be engineered to precisely target and eliminate autoreactive immune cells that drive these debilitating diseases, particularly those affecting the nervous system such as Multiple sclerosis, Myasthenia gravis, Neuromyelitis optica, Stiff-person syndrome, Autoimmune encephalitis, MOG-antibody disease and Chronic inflammatory demyelinating polyneuropathy. Also, through an analysis of preclinical and clinical data, we will assess the efficacy, safety, potential side effects and limitations of these innovative therapies. Lastly, we will underline the transformative potential of CAR T-cells in Autoimmune Neurology, offering a promising new hope for treatment where conventional therapies have failed.